The American Council of Economic Advisers and the German Sachverstaendigenrat a Study in the Economics of Advice - Wallich, Henry C. (Quarterly Journal of Economics, 1968)
Introduction, 349. — Objectivity or maximization? 351. — Goals and their sources, 353. — Goals and instruments, 357. — Sources of influence, 365. — Maximizing effectiveness of advice, 369. — Analytical approaches, 375.